2020
DOI: 10.1002/mnfr.202000517
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Strategy for Simultaneous Quantification of Urine Metabolites to Validate Development of a Biomarker Panel Allowing Comprehensive Assessment of Dietary Exposure

Abstract: Scope: Metabolites derived from individual foods found in human biofluids after consumption could provide objective measures of dietary intake. For comprehensive dietary assessment, quantification methods would need to manage the structurally diverse mixture of target metabolites present at wide concentration ranges. Methods and results: A strategy for selection of candidate dietary exposure biomarkers is developed. An analytical method for 62 food biomarkers is validated by extensive analysis of chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…A comprehensive list of potential urinary BFIs based on a literature analysis ( 53 ) of putative dietary exposure biomarkers in various human biofluids is presented in Supporting Data 2 . The present biomarker panel strategy aimed to assess habitual diet in individuals and populations; key to this objective was the need to use spot urine samples, specifically urine samples collected just before bedtime and FMV urines, that would be informative of overall food consumption ( 1 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A comprehensive list of potential urinary BFIs based on a literature analysis ( 53 ) of putative dietary exposure biomarkers in various human biofluids is presented in Supporting Data 2 . The present biomarker panel strategy aimed to assess habitual diet in individuals and populations; key to this objective was the need to use spot urine samples, specifically urine samples collected just before bedtime and FMV urines, that would be informative of overall food consumption ( 1 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous analysis of published literature revealed that the great majority of dietary exposure biomarker candidates were detected and quantified using LC-MS technology ( 53 ). Chemical classification of putative biomarkers showed great structural diversity that included metabolites from 17 Chemical Classes representative of 7 Chemical Super-Classes ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations